KONTRIBUSI FAKTOR FISIKA KELAUTAN TERHADAP PEMBUDIDAYAAN RUMPUT LAUT (EUCHEUMA COTTONII) DI DESA RIA BAO KECAMATAN NAGAWUTUNG KABUPATEN LEMBATA - Tolok, Yohanes Megu; Wulakada, Hamza Huri; Rahmawati, Arfita (Universitas Nusa Cendana, 2023)
Research Objectives To determine the contribution of marine physics factors to the cultivation of seaweed (Eucheuma cottonii) in Ria Bao Village, Nagawutung District, Lembata Regency.This type of research uses quantitative research. The population in this study is the coastal area of ​​Ria Bao Village, Nagawutung District, Lembata Regency. The sample in the study was taken from the entire population, namely there are three points for determining the location of seaweed cultivation in the coastal area of Ria Bao Village, Nagawutung District, Lembata Regency. The three points were chosen intentionally (purposive sampling). It is planned to measure marine physical factors with a distance of 0.5 to 1 km from the shoreline to the sea, or a depth limit that is still possible for the development of seaweed cultivation.Data sources consist of primary data and secondary data. Data collection techniques are observation, and documentation. The analysis technique is using matrix of land suitability for seaweed cultivation. Research Results (1) The Contribution of Marine Physics Factors to Seaweed Cultivation is the Current Speed Factor (point 1=0.18m/s, point 2=0.30m/s, point 3=0.21m/s), Sea Depth (point 1=3.81 m, point 2=1.93 m, point 3=3.57 m), Brightness (point 1=2.80 m, point 2=1.20 m, point 3=1.60 m) , Temperature (point 1=290C, point 2=300C, point 3=300C), and tides (0.30 m) .